Police officer physical fitness to work: A case for health and fitness training - Ciara Losty (Journal of Human Sport and Exercise, 2017)
There is no reference point currently available to the Irish police force (An Garda Síochána) for measurement of baseline physical fitness or for tracking its current members, as no such data exists. Currently there is no defined health and fitness policy or strategy following a trainee Irish police force two year training period. Measurements of the various health-related components of physical fitness have been developed and, in some cases, standardised, with good to excellent accuracy and reliability (American College of Sports Medicine (ACSM, 2011), as physiological measures (as a proxy for actual physical fitness) with predictive accuracy of an individual’s health outcomes better than physical activity recall (Bovet et al., 2007).  These measures were utilised within this research to ascertain if there were fitness changes within a group of Irish police force trainees during their period in college training.  An improvement was predicted for the trainee group that was at odds with the actual findings.  The focus of this particular study is to provide the information to establish if there is a need for mandatory health and fitness testing (while allowing for individual differences) for this unique Irish work force.